Hubungan Antara Status Gizi (IMT) dengan Usia Menarche pada Remaja Putri Usia 13-14 Tahun di SMPN 1 Pace Kecamatan Pace Kabupaten Nganjuk - Sumy Dwi Antono (coba, 2015)
The average of menarche young women continoued to decline on average about 3-4 months every 10 years. The shift of the age of menarche to younger age can cause emotional stress, the risk of breast cancer, pregnancy is noy on purpose. The purpose of this research is to know the relationship between nutritional status with age of menarche in young women aged 13-14 years. The type of this research use cross sectional research design. Sampling technique of this research used proportional stratified random sampling which the research took a random strata in the population, for this research the reseacher using the lottery draw. The researcher abtained samples of 76 responden of total student population of 96. The analysis data of this research is Spearman Rank. The result of the analysis data shows that there is no relationship between nutritional status with age of menarche which the value tcount = 0,647 less than ttable = 1,995. For this research the researcher gives suggestion to the next researcher to develop the factor social media that can influence the age of menarche in girls forther. Keywords : nutritional status, age of menarche, young women